Una gran medida de ‘opinio juris’ y práctica estatal al gusto: ¿la receta de la costumbre internacional contemporánea? (2015)
The social international practice of contemporary international law does not correspond entirely to the one of the establishment of the icj. The world as to 1945 is definitely not the same of the 21st century. Such reality, has undoubtedly transformed international law and its vertebral components. That transformation includes the theory of the sources as a whole and all its kinds. From that perspective, the present research aims to revisit the traditional concept of customary international law by deciphering its two ingredients, in particular that of opinio juris, which will be tested by using contemporary scholarship and jurisprudence. After explaining some of the major difficulties of the classic concept of opinio juris, there will be a description of newer, contemporary and updated concepts. The foregoing will lead the discussion to demonstrate, whether it is in fact required to develop the classic definition of opinio juris, and whether it is suggested that it may be the only ingredient required in the recipe of contemporary customary international law.